2018
DOI: 10.1088/1361-6587/aad38a
|View full text |Cite
|
Sign up to set email alerts
|

The parallel boundary condition for turbulence simulations in low magnetic shear devices

Abstract: Flux tube simulations of plasma turbulence in stellarators and tokamaks typically employ coordinates which are aligned with the magnetic field lines. Anisotropic turbulent fluctuations can be represented in such field-aligned coordinates very efficiently, but the resulting non-trivial boundary conditions involve all three spatial directions, and must be handled with care. The standard "twistand-shift" formulation of the boundary conditions [Beer, Cowley, Hammett Phys. Plasmas 2, 2687(1995] was derived assuming… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Recently, a more accurate parallel boundary condition for stellarator symmetric flux tubes has been derived in Martin et al. (2018). This approach removes the discontinuities present at the ends of the simulation domain in the current conventional treatment, which can be seen at of the curve in figure 1.…”
Section: Geometry Considerations At Low Magnetic Shearmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a more accurate parallel boundary condition for stellarator symmetric flux tubes has been derived in Martin et al. (2018). This approach removes the discontinuities present at the ends of the simulation domain in the current conventional treatment, which can be seen at of the curve in figure 1.…”
Section: Geometry Considerations At Low Magnetic Shearmentioning
confidence: 99%
“…In such circumstances, accurate flux-tube simulations can be performed using the geometry for only one poloidal turn, as was done in , . Recently, a more accurate parallel boundary condition for stellarator symmetric flux tubes has been derived in Martin et al (2018). This approach removes the discontinuities present at the ends of the simulation domain in the current conventional treatment, which can be seen at θ = ±4π of the k 2 ⊥ curve in figure 1.…”
Section: Parallel Correlationsmentioning
confidence: 99%
“…More recent work considered the self-interaction of linear eigenmodes and revealed that their parallel self-interaction can even interfere with the numerical convergence of nonlinear simulations with respect to the domain size [11,12] §. Additionally, it has been explored in gyrokinetic simulations of low magnetic shear stellarators [13,14]. This paper will show that parallel self-interaction can be eliminated by lengthening the simulation domain in the parallel direction to multiple poloidal turns or making the binormal width of the domain large.…”
Section: Introductionmentioning
confidence: 98%
“…In nonlinear simulations, a box in the radial and binormal directions is defined around the central field line defining the FT, and a set of radial and binormal wavenumbers k x and k y are considered. The fulfilment of the periodicity condition in the parallel direction for all the modes considered in the simulation is more restrictive in this case, with a strong influence of the magnetic shear [1,2,22].…”
Section: Computational Domains and Codesmentioning
confidence: 99%
“…The lack of axisymmetry in stellarators introduces complexity at several levels. First, the twist-and-shift boundary condition in flux tube simulations is questionable [2] due to the three-dimensional dependence of the equilibrium quantities affecting micro-instabilities, such as magnetic field line curvature and magnetic shear. As a consequence of this dependence, different flux tubes over a given flux surface are in general not equivalent to each other [3].…”
Section: Introductionmentioning
confidence: 99%